Small things like these eaudiobook - Keegan, Claire (HighBridge Audio, 2021)
The landmark new novel from award-winning author Claire Keegan It is 1985 in a small Irish town. During the weeks leading up to Christmas, Bill Furlong, a coal merchant and family man, faces into his busiest season. Early one morning, while delivering an order to the local convent, Bill makes a discovery which forces him to confront both his past and the complicit silences of a town controlled by the church. Already an international bestseller, Small Things Like These is a deeply affecting story of hope, quiet heroism, and empathy from one of our most critically lauded and iconic writers.